Addressing Transition to Practice: Assessing Perceived Effectiveness of a Competency Based Change to On-Call Responsibilities of Senior Cardiology Residents - Caddell, Andrew James; Bamwoya, Edwin Moses; Moeller, Andrew Donald (Cardiology and Cardiovascular Medicine, 2022)
Background: There has been a paradigm shift in residency training over the last several years wherein Competency by Design (CBD) is being integrated to replace more traditional time-based models of training. The Residency Program Committee (RPC) for the Cardiology training program at Dalhousie University in Halifax, Canada addressed the Transition to Practice stage by approving a trial of adjusting the resident call responsibilities to reflect the transition to CBD curriculum. The goal of this adjustment was three-fold: i. Gradually increase accountability of the senior cardiology resident as they transition to practice; ii. Address a gap in training that allows the senior resident to have a gradual transition to the role of a practicing cardiologist while on call; iii. Allows further evolution of skills and abilities. Methods: A survey was administered to the practitioners involved in this competency based changes to the call responsibilities. Surveys were distributed to the final year Cardiology Residents, Staff Cardiologists, and Senior Internal Medicine residents to assess their experience and opinions of the current, competency-based change of the on-call curriculum. The survey consisted of eleven questions, of which, four were assessed on a Likert scale and 3 were yes/no questions. Results: Four PGY6 cardiology residents, five senior internal medicine residents and eleven staff cardiologists completed the survey. Amongst those who completed the survey there was agreement that the change to the on-call responsibilities improved cardiology residents’ skills, accountability and preparedness to practice. All groups felt the changes were useful for the cardiology training program. There was mild negative effect of perceived accountability by the internal medicine residents. <p style="text-align:justi